From ‘Mundu’ to Kidnapping For Ransom (KFR): evolution of maritime security threats in the East Coast of Sabah - Abdul Rashid Abdul Hamid; Ramli Dollah (2020)
The threat of piracy in Malaysia especially in Sabah is not a new issue as it can be traced back before the formation of the Federation of Malaysia. The terrifying pirates actively engaged in piracies and attack on merchant ships along the Sulu Sea, the Straits of Malacca and the Straits of Singapore all the way to the Bay of Bengal. However, by the year 2000, the threat that was once considered a pirate’s threat had begun to evolve into a new form of threat called Kidnapping for Ransom (KFR). KFR is an abduction of individuals or groups of people for ransom that is rampant in Sabah’s east coast waters. The discussion in this paper will be divided to three parts, first, look at the history of piracy before 1963; second, piracy in the east coast of Sabah after 1963; and third, the emergence of KFR threat after the year of 2000. This article argues that piracy and KFR attacks were carried out by Abu Sayyaf Group (ASG) since 1980’s. In addition, the article also argues that conflicts in the southern Philippines are among the main reason for the continue occurrence of piracy and KFR threat in the east coast of Sabah. In the preparation of this paper, the authors employ qualitative research methods with data acquisition through interview techniques, fieldwork and library research which are supported by government official documents.